Using Satisfiability Modulo Theories to Analyze Abstract State Machines (Abstract) - Veanes, Margus; Saabas, Ando (ABZ'08, 2008)
We look at a fragment of ASMs used to model protocol-like aspects of software systems. Such models are used industrially as part of documentation and oracles in model-based testing of application-level network protocols. Correctness assumptions about the model are often expressed through state invariants. An important problem is to validate the model prior to its use as an oracle. We discuss a technique of using Satisfiability Modulo Theories or SMT to perform bounded reachability analysis of such models. We use the Z3 solver for our implementation and we use AsmL as the modeling language.
This is an extended abstract.